Gut Microbiota Modulate Rabbit Meat Quality in Response to Dietary Fiber - Liu, Boshuai; Cui, Yalei; Ali, Qasim; Zhu, Xiaoyan; Li, Defeng; Ma, Sen; Wang, Zhichang; Wang, Chengzhang; Shi, Yinghua (Frontiers in Nutrition, 2022)
Antibiotics are widely used in gastrointestinal diseases in meat rabbit breeding, which causes safety problems for meat products. Dietary fiber can regulate the gut microbiota of meat rabbits, but the mechanism of improving meat quality is largely unknown. The objective of this study was to evaluate the effects of adding different fiber sources to rabbit diets on the growth performance, gut microbiota composition, and muscle metabolite composition of meat rabbits. A total of 18 New Zealand white rabbits of similar weight (40 ± 1 day old) were randomly assigned to beet pulp treatment (BP), alfalfa meal treatment (AM), and peanut vine treatment (PV). There were 6 repeats in each treatment and all were raised in a single cage. The predictive period was 7 days and the experimental period was 40 days. The results revealed that AM and PV supplementation increased growth performance, slaughter performance, and intestinal development of meat rabbits compared with the BP treatment, and especially the effect of AM treatment was better. The content of butyric acid was increased in PV and AM treatments compared with the BP treatment. The expression of mitochondrial biosynthesis genes of liver, cecum, and muscle showed that AM treatment increased gene expression of CPT1b compared to the BP treatment. In addition, AM and PV treatments significantly increased the microbial diversity and richness compared with BP treatment, and their bacterial community composition was similar, and there were some differences between AM and PV treatments and BP treatment. Metabonomics analysis of muscle showed that AM treatment significantly increased amino acid and fatty acid metabolites compared with BP treatment, which were mainly concentrated in energy metabolism, amino acid metabolism, and fatty acid regulation pathways. Furthermore, through correlation analysis, it was found that there was a significant correlation between rumenococci in the cecum and amino acid metabolites in the muscle. Overall, these findings indicate that AM may affect the body's health by changing its gut microbiota, and then improving meat quality, and the intestinal–muscle axis provides a theoretical basis.